Thin film thermoelectric generators with semi-metal thermoelectric legs - Yujie Zhang; Chaogang Lou; Xiaojian Li; Xin Li (AIP Advances, 2019)
A type of Bi1.5Sb0.5Te3/Sb1.5Bi0.5Te3 thin film thermoelectric generators with semi-metal thermoelectric legs is presented. In order to improve the adaptability of the devices to different occasions, Au thin films are introduced into the thin film thermoelectric legs and separate each leg into two parts. Experimental results show that, because the larger area of Au thin films brings more heat dissipation, the output voltage and the equivalent Seebeck coefficient of the devices decrease with the increasing length and width of Au thin films. Although the output power of the thermoelectric generators is lower than that of conventional ones, the introduction of Au thin films might extend the application of the devices.